NATIONAL IN INCREASING STUDENT KNOWLEDGE THE PLACE OF VALUES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article highlights the issues of introduction of universal and national values into the educational system and their advantage for training improvement. The author emphasizes the national values as a connection link between the past and the present.